Pengaruh Pertumbuhan dan Utang Terhadap Asosiasi Nilai Pasar - Laba dan Nilai Buku Ekuitas - Kumalahadi Kumalahadi (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2003)
This research modifies the Ohlson model (1995) by proposing hypothesis that the interaction between debt and profit, as well as debt and equity, are weakening profit-to-equity association (company’s value). On the contrary, the interaction between growth and profit, as well as growth and equity, are strengthening profit-to-equity association. The hypothesis was tested using 304 companies listed on Jakarta Stock Exchange (JSX) in the period of 1995 to 1998. Based on the univariate and multivariate tests, we found that the results support the Ohlson theory which said that accounting provided an important signal in the statements of owner’s equity, which covers the relationship between balance sheet accounts and income statement accounts known as book to profit and equity value. The other hypotheses are also supported by the data and the results were significance, except for the interaction between growth and profit, which was supported only by the pool data, and by cross-sectional it was significance for the year 1996.